PROGRESSIVE CAPABILITIES OF MULTIMEDIA AND THEIR USE IN THE EDUCATIONAL PROCESS AS AN INTERACTIVE MULTI-CHANNEL COGNITIVE TOOL - Saidova, Zahro; Bakiyeva, F (Журнал математики и информатики, 2022)
Multimedia technologies enrich the learning process, make learning more effective, involving most of the sensory components of the learner in the process of perceiving educational information.